Penyuluhan tentang Bahaya Merkuri yang Terkandung dalam Kosmetik Krim Pemutih Wajah dan Cara Mengidentifikasinya - Lidyawati; Rosa Mardiana (Akademi Farmasi YPPM Mandiri, 2022)
Mercury is an additive that is often added in cosmetics whose function is to produce white, clean, and smooth facial skin instantly. Seeing the instant results, many women continue to use mercury-based cosmetics. Mercury is strictly prohibited from being used in cosmetic preparations, because of its very strong toxicity to the organs of the kidneys, nerves, and brain. The purpose of this community service is to provide information about the mercury contained in cosmetics and explain how to identify the mercury. The method used in this community service is counseling, namely providing information about the use of cosmetics, prohibited and dangerous materials that are often used in cosmetics, and exposure on how to choose safe cosmetics, namely identifying cosmetic preparations visually. Furthermore, students were given a questionnaire with the aim of knowing the students' understanding after being given counseling. The activity was carried out at the Cut Meutia Pharmacy Vocational School. The results of the questionnaire show that 97 percent of students have understood how to choose safe cosmetics and can identify cosmetics visually in cosmetics containing mercury.